2011
DOI: 10.1186/1532-429x-13-32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemic preconditioning in skeletal muscle measured by functional magnetic resonance imaging and spectroscopy: a randomized crossover trial

Abstract: BackgroundNuclear magnetic resonance (NMR) imaging and spectroscopy have been applied to assess skeletal muscle oxidative metabolism. Therefore, in-vivo NMR may enable the characterization of ischemia-reperfusion injury. The goal of this study was to evaluate whether NMR could detect the effects of ischemic preconditioning (IPC) in healthy subjects.MethodsTwenty-three participants were included in two randomized crossover protocols in which the effects of IPC were measured by NMR and muscle force assessments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 42 publications
(49 reference statements)
2
67
0
Order By: Relevance
“…They found significant correlations of T2 with P i and pH during plantar flexions. In other studies where both 31 P MRS and S EPI were acquired in exercising muscle, the rather large volume of interest was defined based on the sensitive volume of a single loop coil . In our previous work , studying ischaemic exercise, S EPI and 31 P spectroscopy were not measured on the same day.…”
Section: Discussionmentioning
confidence: 99%
“…They found significant correlations of T2 with P i and pH during plantar flexions. In other studies where both 31 P MRS and S EPI were acquired in exercising muscle, the rather large volume of interest was defined based on the sensitive volume of a single loop coil . In our previous work , studying ischaemic exercise, S EPI and 31 P spectroscopy were not measured on the same day.…”
Section: Discussionmentioning
confidence: 99%
“…MRS may improve our understanding of the pathophysiology underlying statin induced myopathy. In a study of healthy subjects, changes in 31-P MRS were measured with leg ischemia resulting from tourniquet application and found that ischemic preconditioning positively influenced the phosphocreatine production during reperfusion 31 .…”
Section: Energetics and Metabolismmentioning
confidence: 99%
“…To date, there are few human studies, but trials suggest that different organ in human such as heart, liver, lung and skeletal muscle acquire protection after ischemia/reperfusion (Sjostrom et al, 1980;Ali et al,2007;Cheung M et al, 1996;Kharbanda et al, 2002). It has been showed that ischemic preconditioning positively influenced muscle metabolism during reperfusion, and this, results in an increase in phosphocreatin production and higher oxygen consumption (Andreas et al, 2011).…”
Section: Ischemic Pre-and Post-conditioningmentioning
confidence: 99%